Child and adolescent psychiatrists and residents in Thailand utilizing the practice of psychostimulant drug holidays in children with ADHD. - Klomchan , T.; Pityaratstian , N. (Chulalongkorn Medical Journal, 2023)
Background : Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common problems in child and adolescent psychiatry worldwide. Psychostimulants are the recognized first-line choice of pharmacotherapy. So far there has been no definitive recommendation about the use of drugs, especially over the holiday. This controversy has resulted in different practices among physicians as to whether they should continue or discontinue the drug over the holiday. Objective : This cross-sectional descriptive study aims to evaluate the practice of psychostimulant drug holidays in children with ADHD among child and adolescent psychiatrists and residents in Thailand and the factors considered in their decision making including the attitudes of physicians toward using psychostimulant drugs in ADHD children. Method : We designed questionnaire to classify three groups of physicians’ practice over the drug holiday: always continue drug; always prescribe drug holiday; consider drug holiday on a case-by-case basis; examine all possible factors that might affect physicians’ decisions, including attitudes about using psychostimulant drugs. The total target population was one hundred and eighty-two physicians including one hundred and sixty-four child and adolescent psychiatrists and eighteen residents with whom we had contact information. Result : One hundred and thirty-two questionnaires were returned from one hundred and fourteen child and adolescent psychiatrists and eighteen residents. Among the respondents, one hundred and sixteen (87.9%) had positive attitudes toward the use of the drugs. The numbers of physicians in the three groups were: twenty-seven (20.5%) always continue the drug; four (3.0%) always prescribe the drug holiday and one hundred one (76.5%) considered the drug holiday on a case-by- case basis. Factors that most affect physicians’ decisions were: the patient’s loss of appetite (mean score = 4.2 out of 5, SD. = 0.95); severity of ADHD symptoms (mean = 4.1, SD. = 1.15); other adverse effects from drug (mean = 4.1, SD. = 1.12). We also found that the school attended during subspecialty training was a statistically significant factor which that affects the resident’s practice (p = 0.007). Our research showed trends that younger physicians are likely to prescribe and continue the drugs when compared to the work experience of the three practice groups (mean working years = 9.2, 12.8 and 7.8 respectively). Conclusion : Our findings suggest that most physicians have positive attitudes in using psychostimulants. The practice of a drug holiday is still unclear. Factors concerning the practice, such as drug adverse reaction and long-term outcome of various treatments should be considered for further study to offer the best benefit to our patients.